Capacity building in low- and middle-income countries: The essentials of sustainable education programs. Issue 8 (August 2022) - Silvers, Rebecca; Watters, Rick; Van Meter, Jessica
Abstract: NPs are an essential resource in the organization and creation of capacity-building efforts to improve healthcare across the globe. There are limited data to guide the creation of effective supplementary education projects. Recent evidence highlights the essential components of sustainability, curriculum development, and program evaluation. Abstract : NPs are an essential resource in the organization and creation of capacity-building efforts to improve healthcare across the globe. There are limited data to guide the creation of effective supplementary education projects. Recent evidence highlights the essential components of sustainability, curriculum development, and program evaluation.